2020
DOI: 10.1186/s13223-020-00446-w
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis to three humanized antibodies for severe asthma: a case study

Abstract: Background: Omalizumab, mepolizumab, benralizumab, and dupilumab are the currently available biologics used to treat asthma in Japan. Anaphylaxis following treatment with mepolizumab or benralizumab is considered rare. Case presentation: We report the case of a 35-year-old woman with severe asthma, who experienced anaphylaxis following the administration of benralizumab, mepolizumab, and omalizumab, separately. The therapy with biologics was chosen to avoid the repeated use of systemic corticosteroids for asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…A previous study reported that omalizumab associated with an estimated 0.1-0.2% of the anaphylaxis incidence [17]. Mepolizumab and benralizumab also demonstrated a risk of anaphylactic reactions in previous studies [18,19], which is consistent with our ndings. Regarding reslizumab, the incidence of anaphylaxis in clinical trials was approximately 0.3% bur there were only 315 cases of total AEs; therefore, more reports were required to determine the association with anaphylactic reactions [14].…”
Section: Discussionsupporting
confidence: 93%
“…A previous study reported that omalizumab associated with an estimated 0.1-0.2% of the anaphylaxis incidence [17]. Mepolizumab and benralizumab also demonstrated a risk of anaphylactic reactions in previous studies [18,19], which is consistent with our ndings. Regarding reslizumab, the incidence of anaphylaxis in clinical trials was approximately 0.3% bur there were only 315 cases of total AEs; therefore, more reports were required to determine the association with anaphylactic reactions [14].…”
Section: Discussionsupporting
confidence: 93%
“…As to mepolizumab, clinical trials of mepolizumab showed no cases of drug‐related anaphylaxis; 18 however, our results found that mepolizumab had a low but positive anaphylaxis signal. In addition, a case of anaphylaxis following the administration of mepolizumab was recently reported by Jingo et al., 19 and more cases might be observed with the extension of the monitoring period. Thus, we also need to be aware of the risk of anaphylaxis with mepolizumab during its clinical application.…”
Section: Discussionmentioning
confidence: 89%
“…A patient in the present study experienced anaphylaxis with three biologics, improved markedly after BT, and now participates in amateur swimming. 31 In addition, the success of some of our patients in discontinuing systemic steroids and benralizumab one year after BT indicates the potential of BT to alleviate the side effects associated with systemic steroids, as well as the financial and overall burden of the disease burden experienced by individuals with severe asthma.…”
Section: Discussionmentioning
confidence: 88%